PhyLab – a virtual reality laboratory for experiments in physics: a pilot study on intervention effectiveness and gender differences - Korlat, Selma; Kollmayer, Marlene; Haider, Christian; Hlavacs, Helmut; Martinek, Daniel; Pazour, Patrick; Spiel, Christiane (Frontiers in Psychology, 2024)
Introduction New technologies have great potential to facilitate students’ understanding and appreciation of one of the most abstract and challenging school subjects – physics. This study aimed to examine the effects of a game-based virtual reality teaching method on secondary school students’ self-beliefs, interest, and performance in physics through a quasi-experimental design using pre- and post-test data. The evaluation is based on the systemic actiotope model that explains a person’s goal-oriented actions by an interplay of their environment, action repertoire (i.e., students’ performance and interest in physics), and subjective action space (i.e., students’ self-efficacy, self-concept, and implicit theories regarding physics). Method A game-based virtual reality App to be used with Google cardboards was developed containing 10 teaching units from the secondary school physics class curriculum. Participants in the control group were taught using traditional teaching methods, while students in the experimental group went through the VR with the teacher and conducted the prepared VR experiments in addition to the traditionally presented content. Three tests measured students’ physics performance during the semester. In addition, students answered questionnaires assessing their interest, self-efficacy, self-concept, and entity implicit theories regarding physics before and after the intervention, resulting in a Pretest-Posttest Control Group Design. Results There were no significant differences between the control and experimental group in test scores on the first and second tests but compared to the control group, the experimental group achieved higher scores on the third test. In addition, the results indicate differential effects of the game-based virtual reality teaching method on students’ interest and self-efficacy regarding physics to the advantage of students identifying as male, but no effects on students’ self-concept, and entity implicit theories regarding physics. Discussion The results of our pilot study suggest that incorporating innovative didactic methods into secondary school physics classes could potentially contribute to higher performance in and motivation for physics during this crucial period of adolescence when students develop educational and career aspirations. However, game-based virtual reality teaching methods seem to favor students identifying as male, which should be considered in their development and presentation. Other practical implications for practitioners and researchers are discussed.